Asymmetric replication of duck hepatitis B virus DNA in liver cells: Free minus-strand DNA. - Mason, W S (1982)
In order to study the replication of the DNA genome of duck hepatitis B virus, an avian virus related to human hepatitis B virus, we have characterized viral DNAs present in the livers of viremic ducks by agarose gel electrophoresis and the Southern blot procedure. In addition to relaxed circular DNA similar to virion DNA, livers contained a heterogeneous population of rapidly migrating species. The conformation of the rapidly migrating species was markedly sensitive to salt, suggesting that these species were largely single stranded. The largest major rapidly migrating species was shown to have an electrophoretic mobility that was insensitive to preheating of the DNA to 100 degrees C and was similar to that of denatured virus DNA 3 kilobases long, suggesting that this DNA was a single-stranded copy of the entire virus genome. Hybridization with strand-specific probes demonstrated that this 3-kilobase species, as well as more rapidly migrating DNAs, were predominantly minus strands.